University scholarship activities on module evaluation questionnaires at a British University - Junko Winch (Higher Education Evaluation and Development, 2022)
Purpose – The purpose of this study comprises the following three: (1) to ascertain the purpose of university module evaluation questionnaires (MEQs) and its reliability; (2) to evaluate University X's MEQ; and (3) to offer how Universities may be able to support their teaching staff with scholarship activities using the MEQ project. Design/methodology/approach – University MEQ purposes and its reliability were investigated using literature reviews. The University X's MEQ seven statements were evaluated by three university academic staff. The study was conducted at a British university in South East of England. The duration of this interdisciplinary project was for two months which was a university interdisciplinary project between 14/07/20 and 13/10/20. Findings – The purpose for MEQs includes (1) students’ satisfaction; (2) accountability for university authority and (3) teaching feedback and academic promotions for teaching staff. The evaluation of University X's MEQ indicated that MEQ questions were unclear which do not serve reliable student evaluation results. This topic may be of interest to University MEQ designers, lecturers, University Student Experience team, University Executive Board, University administrators and University HR senior management teams. Originality/value – The following three points are considered original to this study: (1) MEQ purposes are summarised by students, university authority and teaching staff; (2) the evaluation of a British University MEQ; (3) provides suggestions on how lecturers' scholarship activities can be supported by the university-wide initiative and umbrella network. These are practical knowledge for the faculty and administrators of higher education institutions which may be of use.